2000
DOI: 10.1021/tx990184z
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Function Modeling of the Interactions of N-Alkyl-N-hydroxyanilines with Rat Hepatic Aryl Sulfotransferase IV

Abstract: Although previous investigations have clearly shown that N-hydroxy arylamines and N-hydroxy heterocyclic amines are substrates for sulfotransferases, relatively little is known about which structural features of the N-hydroxy arylamines are important for sulfation to occur. The purpose of this investigation was to determine the extent to which secondary N-alkyl-N-hydroxy arylamines interact with aryl sulfotransferase (AST) IV (also known as tyrosine-ester sulfotransferase or ST1A1) and to evaluate these intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…As a result of this progress made in the determination of sulfotransferase structures and the common structural features of all sulfotransferase structures examined to date, we have conducted homology modeling and substrate/inhibitor-docking studies on AST IV. 19 These crystal structures have also contributed to our knowledge of the sulfotransferase reaction mechanism. 38 Cocrystallization of mEST with the PAP-vanadate complex as a transition state mimic, coupled with mutational analysis, confirmed that the sulfotransferase-catalyzed reaction proceeds by an in-line sulfuryl transfer reaction from PAPS to the substrate.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result of this progress made in the determination of sulfotransferase structures and the common structural features of all sulfotransferase structures examined to date, we have conducted homology modeling and substrate/inhibitor-docking studies on AST IV. 19 These crystal structures have also contributed to our knowledge of the sulfotransferase reaction mechanism. 38 Cocrystallization of mEST with the PAP-vanadate complex as a transition state mimic, coupled with mutational analysis, confirmed that the sulfotransferase-catalyzed reaction proceeds by an in-line sulfuryl transfer reaction from PAPS to the substrate.…”
Section: Introductionmentioning
confidence: 93%
“…Many catecholamines, 11 tyrosine esters, 11 peptides with N-terminal tyrosines, 11 hydroxamic acids, 11,[18][19][20][21] oximes, 22,23 benzylic alcohols, 17,24 and nitroalkanes 14,15,25 are substrates for the enzyme. Sulfuric acid esters of several AST IV substrates, such as those derived from some arylhydroxamic acids, benzylic alcohols, and N-hydroxyarylamines, are known to give rise to cellular necrosis and chemical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies on 1,2,3,4-tetrahydro-1-naphthol and 2-naphthol in the active site of the rat AST IV were performed using the SYBYL molecular modeling package (SYBYL version 6.7; Tripos Inc., St. Louis, MO) running on a Silicon Graphics O2 workstation (SGI, Mountain View, CA). A previously developed homology model of AST IV (King et al, 2000) was used as the basis for all docking and energy minimization calculations. Coordinates for modeling an estradiol molecule at the sulfuryl acceptor site were obtained from the structure of a mouse estrogen sulfotransferase-17␤-estradiol-PAP complex (PDB crystal structure code: 1AQU) (Kakuta et al, 1997).…”
Section: Fig 1 Structures Of the Isomers Of 1234-tetrahydro-1-namentioning
confidence: 99%
“…A homology model for AST IV has been previously developed (King et al, 2000) based on the electron density map of mouse estrogen sulfotransferase (Kakuta et al, 1997). Mouse estrogen sulfotransferase serves as a particularly good structure for homology modeling of AST IV due to the availability of crystal structures that include enzyme-substrate and enzyme-product complexes as well as the structure of an enzyme-PAPvanadate complex that serves as a transition state model (Kakuta et al, 1998).…”
Section: Homology Modeling Of Ast IVmentioning
confidence: 99%
See 1 more Smart Citation